RodZ modulates geometric localization of the bacterial actin MreB to regulate cell shape - Alexandre Colavin (Nature Portfolio, 2018)
Membrane protein RodZ interacts with the actin-like protein MreB, which coordinates cell-wall insertion to maintain the typical rod-like shape of E. coli cells. Here, the authors provide evidence that RodZ modulates the biophysical properties of MreB and alters the spatial organization of cell-wall growth.